(3GdUMjaI GdSLGOjIs - (3Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH, GdgGTej GdbQTj, CHh GdMSf, GdedbH HRjf GdYGHOjf , (B94 (3g` s ((3eMeO jMji GdgeOGfjs)
(3ChdgG (B:s
(3eHJhQI GdChd, hChd GdehLhO efgG bhdg(B: (3bGd CNHQfG GdTjN GdSYjO CHh YHO Gddg eMeO Hf CMeO Hf TgQjGQ GdNGRf(B...s
(3BNQgG (B:s
...(3jG MGaXG dG jZad (B...(3GdZhK GdZhK NdUfG ef GdfGQ jGQHs
(3JMJ cd SWQ JQLeJg HGdaGQSjIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJhMjO hGdedd hGdfMds